Stuck Prosthetic aortic and mitral valves in pregnancy: Thrombolysis with streptokinase - Karki, Biplave; Sharma, Chitra Raj; Joshi, Shristi; Shrestha, Purna Radha (Nepal Mediciti Medical Journal, 2024)
Despite improvements in the design of prosthetic heart valves and the use of anticoagulation, stuck valve due to thrombosis remains the most dreaded complication of mechanical heart valve replacement. Discontinuation of anticoagulation during pregnancy due to fear of congenital anomaly as a result of inadequate counseling remains a great challenge. A course of thrombolytic therapy may be considered as a first-line therapy for prosthetic heart valve thrombosis. The safety of thrombolysis in pregnancy is not known. We describe a multigravida with mitral and aortic valve replacement status presenting with acute prosthetic mitral and aortic valve thrombosis and treated successfully with intravenous streptokinase.